The Process of Becoming an Embedded Curriculum Librarian in Multiple Health Sciences Programs. - Wilson, Gwen (Medical Reference Services Quarterly)
Higher education is moving to offer more fully online programs, and the health science fields are no different. These programs are either hybrid or completely online. It is up to the health sciences librarian to adapt services offered by the academic library to these types of courses. This column discusses the multiple ways a librarian can be an embedded librarian in a course using a learning management system (LMS). The process of creating a customized embedded librarian program, results, and lessons learned from the different embedded librarian roles are also discussed.